Konsep jiwa menurut Fakhr al-Din al-Razi: Terjemahan dan analisis Kitab al-Nafs wa al-Ruh wa Sharh Quwahuma / Mohd Manawi Mohd Akib - Mohd Manawi , Mohd Akib (2018)
Discussion on the concept of human soul or human psychology should touch the spiritual and physical aspects in line with the nature of the human being which consists of those two aspects. But today's discussion on the discipline of psychology, which is dominated by western thinkers, does not imply to know the true nature of human beings as a result of the neglect of the spiritual aspect, and even unable to solve daily growing psychological problems. Therefore, a research has been conducted to present a discussion on the concept of soul based on Muslim thinkers’ thought who emphasize more on the spiritual aspect in order to accommodate the existing discussion on psychology. This research aims to analyse Fakhr al-Din al-Razi’s thoughts on the concept of soul based on his work Kitab al-Nafs wa al-Ruh wa Sharh Quwahuma. The thesis is divided into five chapters, the first chapter is on the introduction, the second chapter discusses about the concept of soul according to Muslim thinkers, followed by the third chapter presents the text translation and annotation of the Kitab al-Nafs wa al-Ruh wa Sharh Quwahuma, whereas, the fourth chapter contains findings of data analysis, and lastly the fifth chapter is on conclusion. This study was based on a literature study using qualitative methods of descriptive analysis through the documentation method in collecting important data and content analysis methods in analysing the data. These methods apply specifically to al-Razi’s main work and his other works as well as to other views of selected Muslim thinkers, Ibn Sina and al-Ghazali as a theoretical framework. The research puts an effort to translate and analyse the nine chapters of Kitab al-Nafs wa al-Ruh wa Sharh Quwahuma which be composed of discussions on the concept of soul. The research finds that there are four main themes emphasized by al-Razi namely the essence of the soul, the relationship of the soul to the body, the potential of the soul and the happiness of the soul. Al-Razi disputes that the soul is a essence that is new, permanent and different from the body. It is also the manager and director of the body through spirit that centred in the heart. All the potential of souls and all body parts are the tools for the soul and the mental pleasures are nobler and more perfect than the sensual pleasures. In the hereafter, the soul will be resurrected with the body to receive rewards and retribution whether it is happiness or misery. The happiness achieved by the soul and the body in the hereafter is the ultimate happiness and vice versa.